Analisis Pengaruh Kualitas Layanan Terhadap Kepuasan Penumpang Dan Dampak Terhadap Loyalitas Penumpang Pengguna Jasa Transportasi Kereta Api Pelabuhan Merak - Rangkasbitung (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2023)
As a means of transportation, trains can transport large quantities of goods and are very beneficial to society, so it is very appropriate to support their development. Transportation development is reflected in passenger satisfaction with the restoration of rail transit. Therefore, this study examines railway passenger satisfaction and impact on passenger loyalty. The variables used in this study are Tangible (X1), Reliability (X2), Assurance (X3), Empathy (X4), Responsiveness (X5), Passenger Satisfaction (Y) and Passenger Loyalty (Z) . The method used in this study uses a structural equation modeling (SEM) program using the smart-PLS 3.0 tool. Structural equation modeling is a multivariate statistical technique that combine factors analysis and regression analysis (correlation analysis) to study the relationship between variables in the model. This study identifies the variables that are significant for passenger satisfaction (Y) and passenger loyalty (Z). Based on the results of this study that there are three variables that are significant for passenger satisfaction (Y) and passenger satisfaction (Y) that are significant for the loyalty of passengers (Z).